ISI SURAKARTA HOLDS TRAINING TO EMPOWER AISYIYAH RESIDENTS INCREASE THE TRADE VALUE OF TYPICAL KARANGANYAR SOUVENIRS - Sunarmi, Sunarmi; Handriyotopo, Handriyotopo; Raden Ersnathan Budi Prasetyo; Reno Abdurrahman; Yuninggar Renaningtyas; Nova Wulan Priyandani (Bajang Institute, 2023)
Packaging is an important element in maintaining food quality and safety. Aisyiyah is a women's organization that exists to support the government in various fields, one of which is the welfare of the people through the Economic and Welfare Council in developing and marketing food that has economic value as tourist souvenirs. The obstacle faced is the weak packaging design. Training and empowerment in visual merchandising design management was carried out for Aisyiyah residents in Karanganyar. Aisyiyah residents as a partnership network of lecturers under LPPMPP ISI Surakarta handle problems with training assistance from the design and postgraduate departments. The strategy chosen for empowerment is ecologically based, using the Rapid Rural Appraisal (RRA) Method. In this method, participants are invited to learn to understand the potential and awareness of maintaining environmental safety, and are able to build motivation for EcoDesign creativity. The Participatory Rural Appraisal (PRA) method emphasizes participant involvement in being able to foster creativity related to the personal potential of traders, building creative interior design abilities, especially related to merchandise image. The results of the empowerment training consist of (1) participants' skills in analyzing packaging design needs for culinary businesses; (2) The creative results of merchandise packaging designs consist of snacks, side dishes, bags, batik in the concept of plastic wrap, paper, and environmentally friendly rattan bags and paper bags. Empowerment activities can be utilized: (1) Recommendations on design offers for group businesses; (1) Providing participants with skills and knowledge in developing culinary businesses independently